CHANGES IN PHARMACOKINETIC PROPERTIES OF ANTIBACTERIAL DRUGS IN CRITICALLY ILL PATIENTS - Agnieszka Małgorzata Cios; Anna Wesołowska (Polish Pharmaceutical Society, 2020)
Critically ill patients are at high risk of developing a life-threatening infection leading to severe shock and, as a consequence, multi-organ failure and even death. Optimal antimicrobial therapy, especially in the first 48 hours, is crucial to increasing patients' chances of survival. However, effective drug dosing is problematic because pathophysiological changes associated with the critical state of a disease affect their pharmacokinetic properties, mainly those drugs that are hydrophilic in nature. Concentrations of these drugs may be elevated in critically ill patients, mainly because of decreased renal clearance due to renal failure/damage. Conversely, antimicrobial concentrations may decrease due to increased volume of distribution and increased renal clearance, caused by the systemic inflammatory response syndrome, capillary leakage, reduced drug binding, intravenous fluids and inotropic drugs used. The frequency of simultaneous occurrence of numerous complications that may affect pharmacokinetic properties of drugs is excessively complicated by predicting their therapeutic concentrations. In general, situations where antimicrobial concentrations in serum of critically ill patients are too low dominate in clinical settings. And obtaining inappropriate plasma concentrations of patients is clinically important because it leads to ineffective eradication of pathogenic microorganisms and a lack of clinical improvement. In addition, too low drug levels trigger the development of multi-drug resistance, which is not only a medical but also a socio-economic problem. One of the major solutions to this problem seems to be the widespread use of plasma drug monitoring for individual adjustment of the dosage of antimicrobial drugs in a particular patient's clinical condition. However, despite the successful implementation of the beta-lactam antibiotic monitoring program in critically ill patients in Poland, several problems remain to be solved, such as insufficient documentation of the advantage of such a procedure and its clinical success, the lack of necessary technical preparation and specialist knowledge of medical staff in hospitals, which has an impact for the time of determining the concentration of antibacterial drugs in the patient plasma, even the possibility of monitoring drug concentration therapy does not solve the problem of obtaining the most optimal pharmacokinetic-pharmacodynamic indicators that determine the dosage selection. One solution, though not without its drawbacks, is to use population models to calculate the dosage of antimicrobial drugs. These models should take into account the state of mechanical ventilation, diagnostic category and glomerular filtration of the patient. However, also in such model preparation, there are problems such as the state of patients' kidney function, which may show large fluctuations and require frequent monitoring of creatinine, which is associated with additional work and time input, capillary leak affecting the value of distribution volume. The above pathophysiological changes significantly impede the development of appropriate models that would be adequate for use in optimization of the antimicrobial dosage in critically ill patients.